Changes in ceramide metabolism are essential in Madin-Darby canine kidney cell differentiation - Pescio, Lucila Gisele (J Lipid Res, 2017)
Ceramides (Cers) and complex sphingolipids with defined acyl chain lengths play important roles in numerous cell processes. Six Cer synthase (CerS) isoenzymes (CerS1–6) are the key enzymes responsible for the production of the diversity of molecular species. In this study, we investigated the changes in sphingolipid metabolism during the differentiation of Madin-Darby canine kidney (MDCK) cells. By MALDI TOF TOF MS, we analyzed the molecular species of Cer, glucosylceramide (GlcCer), lactosylceramide (LacCer), and SM in nondifferentiated and differentiated cells (cultured under hypertonicity). The molecular species detected were the same, but cells subjected to hypertonicity presented higher levels of C24:1 Cer, C24:1 GlcCer, C24:1 SM, and C16:0 LacCer. Consistently with the molecular species, MDCK cells expressed CerS2, CerS4, and CerS6, but with no differences during cell differentiation. We next evaluated the different synthesis pathways with sphingolipid inhibitors and found that cells subjected to hypertonicity in the presence of amitriptyline, an inhibitor of acid sphingomyelinase, showed decreased radiolabeled incorporation in LacCer and cells did not develop a mature apical membrane. These results suggest that hypertonicity induces the endolysosomal degradation of SM, generating the Cer used as substrate for the synthesis of specific molecular species of glycosphingolipids that are essential for MDCK cell differentiation.